Modelling the effect of national culture on multinational banks' performance: A conditional robust nonparametric frontier analysis - Halkos, George Emm; Tzeremes, Nickolaos G. (Economic modelling, 2011)
Most of the efficiency studies of large multinational banks operating in different countries calculate banks' inefficiency levels without taking into account the environmental factors in which they are operating in. As a result the estimated inefficiencies are subject to a combination of true managerial inefficiencies and the impact of environmental factors which most of the time are not appropriately controlled in the analysis. This study by examining 282 multinational banks from 43 different countries calculates the influence of their national culture on their estimated efficiency levels. By using conditional and unconditional robust efficiency estimators this paper provides empirical evidence of how different cultural values influence banks' global practices and thus their performances. The results indicate that there is a cultural pattern that has a positive effect on banks' performance. That is lower masculine, uncertainty avoidance and power distance values and moderate individualistic values.